Cloning and Expression of hGAD65 Gene in E. Coli BL21 - Rista Nikmatu Rohmah; Soraya Widyasari; A. Aulanni’am; F. Fatchiyah (Indonesian Journal of Biotechnology, 2013)
The aim of this study is to construct the hGAD65 gene and to identify the hGAD65 clone by using PCR & RFLP. The samples were derived from normal person & DM patient’s blood. Blood DNA was isolated by salting out method and then amplified by PCR with a pair of specific primer, GAD65-F-BamH1-807 & GAD65-R-Xho1-945. The PCR-product was cloned into vector pET-28a and the pET28a-hGAD65-clone was transformed into E.coli BL21 competent cells. The pET28a-hGAD65-clone was confirmed by PCR and RFLP by BamH1 & XhoI. The PCR product of pET28a-hGAD65-clone was one band of 159bp and has two bands 5.3 kb and 159 bp by RFLPwith both restriction enzymes. The GAD65 protein is expressed in 65kD of pET28a-hGAD65-clone. PET28a-hGAD65-clone was able to recognize by gold standard monoclonal antibody specifically. These results indicated that the hGAD65 gene inserted into pET28a properly and provided the GAD65 protein expression. Key words: hGAD65, PCR, pET-28a, RFLP